Adsorption structures affecting the electronic properties and photoinduced charge transfer at perylene-based Molecular interfaces [data] - Wirsing, Sara; Hänsel, Marc; Craciunescu, Luca; Rein, Valentina; Schreiber, Frank; Broch, Katharina; Engels, Bernd; Tegeder, Petra (Universität, 2024)
Underlying data for figures in the paper "Adsorption Structures Affecting the Electronic Properties and Photoinduced Charge Transfer at Perylene-Based Molecular Interfaces"
Finanziert durch: Deutsche Forschungsgemeinschaft: SFB 1249: N-heteropolycycles as functional materials: 281029004-SFB 1249, Project B06
Gesehen am 12.02.2024
Keywords: Forschungsdaten; Datenbank